Focal plane model for flat refractive geometry - Mann, Garrett W.; Eckels, Steven J. (My University, 2017)
Flow visualization techniques such as uPIV and droplet imaging determine the measurement volume by the focal plane. Thus, an understanding of how the focal plane moves in reference to the camera is necessary when planar interfaces are present between the camera and the focal plane.
Citation: Mann, G. W., & Eckels, S. J. (2017). Focal plane model for flat refractive geometry. Journal of the European Optical Society-Rapid Publications, 13(1), 39. https://doi.org/10.1186/s41476-017-0067-3
Keywords: Focal plane; PIV; Refractive geometry; Depth of field